Peak load forecasting on national holiday using fuzzy-cuckoo for Jawa-Bali system in Indonesia - Imran, Andi; Made Yulistya Negara, I; Robandi, Imam (International Journal of Engineering and Technology, 2019)
This paper discusses the peak load forecasting on national holiday. The forecasting is done by using Fuzzy Logic System Type 2 method, optimized with Cuckoo Search Algorithm (CSA). Cuckoo Search Algorithm is used to optimize Footprint of Uncertainty (FOU) on fuzzy logic which consisting of antecedent (X, Y) and consequent (Z). This method uses data from daily peak load during the holidays on the Jawa-Bali electricity system. The data is focused on load data from four days before holidays (h-4) and on holidays (h). Validation results indicate that the Fuzzy Logic System Type-2 method which is optimized with Cuckoo Search Algorithm provides a good enough forecasting with Mean Absolute Percentage Error (MAPE) is less than 2%.Â Â
Keywords: Peak Load Forecasting; National Holiday; Fuzzy Logic Type-2; Cuckoo Search Algorithm; MAPE.